Association between live microbe intake and depression in COPD aged 40 years and older: evidence from NHANES 2005–2018 - Gao, Wei; Ling, Xin; Wang, Yan; Zhao, Xiaoxia; Shi, Yushan (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to investigate the association between dietary intake of live microbes and the prevalence of depression among patients with Chronic Obstructive Pulmonary Disease (COPD) aged 40 years and older, using data from the National Health and Nutrition Examination Survey (NHANES) 2005–2018.MethodsThe study included 1,494 participants (representing 9.04 million COPD adults in the U.S.) aged 40 and above. Dietary intake of live microbes was categorized into low, moderate, and high groups based on 24-h dietary recall data. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9) with a score ≥10 indicating depression. Weighted logistic regression analysis was performed to evaluate the association between live microbe intake and depression, adjusting for various covariates. Additionally, subgroup analysis and sensitivity analysis were conducted.ResultsHigher dietary intake of live microbes was associated with a lower prevalence of depression in COPD participants. In the fully adjusted model, compared to the low intake group, the odds ratio (OR) for depression was 0.55 (95% CI: 0.33–0.92) for the high intake group. This inverse association was still statistically significant in individuals under 65 years, males, non-obese individuals, and those without cardiovascular disease. In addition, the results of the sensitivity analysis also indicate relationship stability.ConclusionThis study indicates an inverse association between higher dietary intake of live microbes and the prevalence of depression among COPD patients aged 40 and above in the United States. Future prospective studies are needed to verify this association and explore underlying mechanisms.